2016
DOI: 10.1016/j.epsl.2016.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating controls on planktonic foraminiferal geochemistry in the Eastern Tropical North Pacific

Abstract: between mixed-layer species G. ruber and G. bulloides and thermocline-dweller G. menardii track seasonal changes in upwelling. The records suggest an increase in upwelling during the peak positive phase of El Niño, and an overall reduction in stratification over the six-year period. For all three species, Mg/Ca ratios are higher than what has been reported in previous studies, and show poor correlations to calcification temperature. We suggest that low pH (7.6-8.0) and [CO 3 2− ] values (∼70-120 μmol/kg) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 61 publications
(89 reference statements)
1
19
0
Order By: Relevance
“…For example, G. bulloides has a demonstrated preference for nutrient‐rich waters with high turbidity, and seasonal abundance of G. bulloides is strongly tied to regional upwelling patterns (Abrantes et al, ; Gibson et al, ). Thus, G. bulloides δ18Oc may be strongly skewed to record temperatures from cold, upwelled waters.…”
Section: Resultsmentioning
confidence: 99%
“…For example, G. bulloides has a demonstrated preference for nutrient‐rich waters with high turbidity, and seasonal abundance of G. bulloides is strongly tied to regional upwelling patterns (Abrantes et al, ; Gibson et al, ). Thus, G. bulloides δ18Oc may be strongly skewed to record temperatures from cold, upwelled waters.…”
Section: Resultsmentioning
confidence: 99%
“…Both regressions indicate that Mg/Ca-temperature sensitivity that is much lower than the 9%/°C of the Anand et al (2003) equation, which is the most widely used for down core reconstruction of Mg/Ca-SST. Recent sediment trap studies have also found lower Mg/Ca-temperature sensitivity in G. ruber than the canonical 9%/°C, including a temperature sensitivity as low as 3%/°C in the Gulf of Tehuantepec (Gibson et al, 2016) and 6%/°C in a global sediment trap data set published by Gray et al (2018). These discrepancies likely stem from inherent uncertainties in estimating calcification temperature from δ 18 O or gridded temperature data sets, as well as secondary controls on foraminiferal Mg/Ca (e.g., salinity and pH).…”
Section: 1029/2018pa003417mentioning
confidence: 96%
“…bulloides yielded the most robust validation statistics and suggested a temperature sensitivity of 7.9 ± 0.1% per degree Celsius that broadly agrees with previous calibrations, which show a relatively wide range of sensitivities. Culture (Mashiotta et al, ; Lea et al, ) and some sediment trap data (Jonkers et al, ; Pak et al, ) point to a higher T sensitivity of 9–10% per degree Celsius, while other sediment trap data (Gibson et al, ; McConnell & Thunell, ) and core‐top analyses of individual chambers (Marr et al, ) point to a lower sensitivity of ~6% per degree Celsius. All else being equal, calibrations across a wider T range should better resolve the true T sensitivity, and one possible explanation for the observed range in T sensitivity may be the T range over which calibrations were performed.…”
Section: Discussionmentioning
confidence: 99%